An assessment of differential reinforcement procedures for learners with autism spectrum disorder. Issue 2 (19th January 2017) - Johnson, Kate A.; Vladescu, Jason C.; Kodak, Tiffany; Sidener, Tina M.
Abstract : Differential reinforcement procedures may promote unprompted correct responding, resulting in a quicker transfer of stimulus control than nondifferential reinforcement. Recent studies that have compared reinforcement arrangements have found that the most effective arrangement may differ across participants. The current study conducted an assessment of differential reinforcement arrangements (i.e., quality, schedule, and magnitude) and nondifferential reinforcement to identify the most effective arrangement for each participant. The assessment phase showed that the quality arrangement was the most efficient for all participants during auditory‐visual matching. Next, a validation phase was conducted to evaluate whether the assessment would predict the most effective arrangement across multiple skills. The results from the assessment phase were validated for all participants for the same skill. However, the results were only validated for one participant during the other skills (i.e., tact and intraverbal). The results are discussed in light of previous research and future areas of research.